New directions in information organization - Park, Jung-ran; Howarth, Lynne Christine (Library and information science (New York, N.Y.) ;, 2013)
New directions in information organization, co-edited by Dr. Jung-ran Park and Dr. Lynne Howarth seeks to provide an overview and understanding of the future directions, leading edge theories and models for research and practice in information organization.